Bilobed gallbladder: a rare congenital anomaly of the biliary system - Roul, Pradeep Kumar; Saini, Aditi; Agarwal, Srishti; Verma, Prashant Kumar; Syed, Anjum (International Journal of Research in Medical Sciences, 2021)
Duplication of the gallbladder is a rare congenital anomaly, which Boyden first illustrated in 1926. No additional risk of cholelithiasis or malignancy with this congenital anomaly was documented. However, this congenital anomaly is associated with more risk for complications during and after laparoscopic cholecystectomy. So, preoperative diagnosis is essential in identifying anatomical abnormalities to avoid biliary injuries at the time of surgery or the performance of an incomplete operation. The removal of an asymptomatic double gallbladder remains controversial. Here, we are reporting a case of the incidentally detected duplex gallbladder in a teenager and review the literature that will enrich the reader’s knowledge regarding this rare congenital anomaly.